Search for decays of neutral beauty mesons into four muons - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Malde, S; et al. (Springer, 2017)
A search for the non-resonant decays Bs0 → μ+μ−μ+μ− and B0 → μ+μ−μ+μ− is presented. The measurement is performed using the full Run 1 data set collected in proton-proton collisions by the LHCb experiment at the LHC. The data correspond to integrated luminosities of 1 and 2 fb −1 collected at centre-of-mass energies of 7 and 8 TeV, respectively. No signal is observed and upper limits on the branching fractions of the non-resonant decays at 95% confidence level are determined to be ℬ(Bs0→μ+μ−μ+μ−) < 2.5×10^−9, ℬ(Bs0→μ+μ−μ+μ−) < 6.9×10^−10